2010
DOI: 10.1111/j.1471-1842.2009.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of information skills training on independent literature searching activity and requests for mediated literature searches

Abstract: Background: Most NHS library services routinely offer both mediated searches and information skills training sessions to their users. We analyse the impact of these two services on the amount of literature searching demonstrated by users of hospital-based library services in the north-west of England. Methods: Data for (1) mediated literature searches, (2) number of library users attending information skills training sessions, (3) amount of library staff time devoted to information skills training, and (4) num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…There was however no attempt to measure changes in behaviour or results. On the other hand, Addison et al . found that information skills training was associated with an increased demand for mediated searches, but not with more independent searches.…”
Section: Introductionmentioning
confidence: 99%
“…There was however no attempt to measure changes in behaviour or results. On the other hand, Addison et al . found that information skills training was associated with an increased demand for mediated searches, but not with more independent searches.…”
Section: Introductionmentioning
confidence: 99%
“…Information professionals are involved in creating these databases, and it is part of the librarian's role to ensure that clinicians are informed of their existence and how to search them. However, there is an argument that even with training, the busy clinician will not make the best use of these tools …”
Section: Literature Reviewmentioning
confidence: 99%
“…Although it is possible to debate the precise effectiveness of training (Addison et al 2010), it is largely undisputed that as long as the skills covered in a training session are used with some frequency afterward, the training will be worthwhile in terms of enhancing the knowledge and skills of attendees (Bell 2005;Borgman 1986;Donnelly & Craddock 2007;Haya et al 2006;Carritt 2007;Webber & Johnston 2000;Daughtery & Russo 2011). Practicing the skills learned in a training session seems to "embed what has been learned" (Donnelly & Craddock 2007, p. 56) and is key to attendees retaining the information they learn in training.…”
Section: Value and Effectmentioning
confidence: 99%
“…There is some evidence that users who attend training may become increasingly aware of the complexity of searching (Addison et al 2010;Kuhn 2009), and therefore have a reduced confidence in their own searching ability. This sort of response has not been widely documented however, and where found there was no attempt to establish whether training improved the results found by attendees (Addison et al 2010). In contrast, the advantages users find after attending training have been widely cited (Borgman 1986;Carroll et al 2001;Carritt 2007;Daughtery & Russo 2011;Haya et al 2007;Kuhn 2009), and range from learning information that makes searching more effective, insights that improve work flow and better quality results to searches (Donnelly & Craddock 2007, p. 64).…”
Section: Value and Effectmentioning
confidence: 99%